2014
DOI: 10.1111/tct.12214
|View full text |Cite
|
Sign up to set email alerts
|

Novel clinical learning from a student-led clinic

Abstract: Student-led clinics have clear community benefits by mitigating service gaps while providing experiential learning opportunities. These learning opportunities are perceived to be novel, and may resemble advantages observed in the classroom with problem-based learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 8 publications
(16 reference statements)
3
32
0
Order By: Relevance
“…One scenario that eliminated these typical time constraints is the student-led free clinic. Nationwide, student-led free clinics have been utilized to meet the needs of underserved communities and have received high satisfaction scores from patients and students [8,9]. These models have shown students' increased ownership of patients' experiences [8] and improvement in the students' knowledge and skills [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…One scenario that eliminated these typical time constraints is the student-led free clinic. Nationwide, student-led free clinics have been utilized to meet the needs of underserved communities and have received high satisfaction scores from patients and students [8,9]. These models have shown students' increased ownership of patients' experiences [8] and improvement in the students' knowledge and skills [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing sense of unease regarding the sustainability of clinical education. This is partly due to funding restrictions in the education and healthcare sectors, an exponential growth in student enrolments in physiotherapy entry-level programs, and a decreasing source of clinical education providers (Bostick, Hall, and Miciak, 2014;Crosbie et al, 2002;Hobbs, Henley, Higgs, and Williams, 2000). Additional barriers such as staff shortages, financial limitations, competition between universities, and challenges in delivering quality patient care also impact student clinical placement capacities across wider healthcare settings (Davies, Hanna, and Cott, 2011;Strohschein, Hagler, and May, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, PA scoring functioned purely as a reflective exercise for student assessors. Two prior studies found that peer assessment was a valued student-led approach to assessment strategies, 23,24 but more evidence is needed to support this important assessment tool for future assessment strategies.…”
Section: Resultsmentioning
confidence: 99%